Analysis of maternal near miss cases in a tertiary care hospital - N., Sunanda; R., Sudha; M., Impana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The study of maternal near miss (severe maternal morbidity) is an alternative to study of maternal death. To reduce maternal mortality ratio (MMR), analysis of maternal near miss cases provide valuable information, which helps in implementing strategies to prevent maternal death. Aims and objectives were to determine maternal near miss indices and to analyse the causes of maternal near miss and other associated factors. Methods: A retrospective analysis of health records of maternal near miss cases admitted to tertiary care hospital from October 2021 - September 2022 was done. Patient characteristics like age, parity, gestational age, risk factors, mode of delivery, lifesaving intervention were studied. Results: A total of 9,744 patient admitted for seeking obstetric care and out of which there were 8,791 deliveries. A total of 164 maternal near miss cases and 24 maternal deaths were found during study period. The maternal near miss incidence ratio 18.76/1000 live birth, maternal near miss to mortality ratio 6.8:1 and mortality index was 12.7%. Hypertension and its complications are the most common cause for maternal near miss cases. Women in late trimester, multiparity, low education status, lack of awareness are at increased risk of near miss cases. Conclusions: Hypertensive disorders in pregnancy and obstetric hemorrhage are leading cause for pregnancy specific obstetric disorder and anemia was found to be a leading cause for pre-existing condition aggravated during pregnancy. This study highlights the need for overall improvement in awareness among pregnant mothers and its timely accessibility with quality critical care management.